Performance of an open pollinated population of’ CZP 9603’ pearl millet (Pennisetum glauculm)* - MANGA, V K (The Indian Journal of Agricultural Sciences, 2011)
A pearl millet (Pennisetum glaucum (L.) R. Br emend. Stuntz.) population ’CZP 9603’ was developed at the Central Arid Zone Research Institute, Jodhpur by inter-mating 19 promising full-sib progenies under the variety developlnent programme. In station trials this population recorded 12.6 to 55.3 %higher grain yield and 21.4 to 41.6%higher dry fodder yield over the check varieties. Similarly in All India Coordinated Trials conducted during 1998-2000 ’CZP 9603’ recorded on an average 12.6 to 17.8 %higher grain yield and 19.4 to 27.6% higher dry fodder yield over the national checks. ’CZP 9603’ was thus a dual purpose population that had the potential of meeting food and fodder requirement of the arid region.